IMPLEMENTASI PRINSIP FREEDOM OF SPEECH DALAM REGULASI PEMUTUSAN AKSES INTERNET DI INDONESIA - Safinatul Wahidah (Universitas Halu Oleo, 2022)
This paper aims to review the implementation of the principle of communication policy, freedom of speech in the regulation of internet access termination. Indonesia already has the ITE Law which regulates the policy of internet shutdowns. This means that the internet as an instrument to express freedom of opinion is no longer a free medium because it has been limited by the rule of law. In this study, the researcher uses the principle of freedom of speech communication policy to see the consequences of the law and the problems that may arise as a result of its implementation. This study finds that there is arbitrariness in the implementation of internet shutdowns regulations that are regulated in the ITE Law Article 40 (2a) and (2b) so it needs to be evaluated, reviewed, and revised.